Donors FMO3 polymorphisms affect tacrolimus elimination in Chinese liver transplant patients. (February 2017) - Ren, Lei; Teng, Mujian; Zhang, Tao; Zhang, Xiaoqing; Sun, Bo; Qin, Shengying; Zhong, Lin; Peng, Zhihai; Fan, Junwei
Aim: Flavin-containing monooxygenase (FMO) variants were potentially involved in tacrolimus metabolism in kidney transplantion. The influences of FMO3 genotypes on tacrolimus elimination in Chinese liver transplant patients remained unclear.Patients & methods: FMO3 SNPs and CYP3A5 rs776746 were analyzed in 110 Chinese patients.Results: Donor FMO3 rs1800822 allele T and rs909530 allele T were associated with fast tacrolimus elimination. Combination of polymorphisms of donor FMO3 rs1800822 and rs909530 genotype impacted on tacrolimus elimination (p = 0.0221). The number of donor rs1800822 allele T and rs909530 allele T was confirmed to be an independent predictor of the tacrolimus concentration-to-dose ratios for weeks 2, 3 and 4 in the multivariate analysis.Conclusion: Donor's FMO3 polymorphisms might affect tacrolimus elimination.